Epigenetic and Neurological Impairments Associated with Early Life Exposure to Persistent Organic Pollutants - Nathalie Grova; Henri Schroeder; Jean-Luc Olivier; Jonathan D. Turner (International Journal of Genomics)
The incidence of neurodevelopmental and neurodegenerative diseases worldwide has dramatically increased over the last decades. Although the aetiology remains uncertain, evidence is now growing that exposure to persistent organic pollutants during sensitive neurodevelopmental periods such as early life may be a strong risk factor, predisposing the individual to disease development later in life. Epidemiological studies have associated environmentally persistent organic pollutant exposure to brain disorders including neuropathies, cognitive, motor, and sensory impairments; neurodevelopmental disorders such as autism spectrum disorder (ASD) and attention-deficit hyperactivity disorder (ADHD); and neurodegenerative diseases including Alzheimer’s disease, Parkinson’s disease, and amyotrophic lateral sclerosis (ALS). In many ways, this expands the classical “Developmental Origins of Health and Disease” paradigm to include exposure to pollutants. This model has been refined over the years to give the current “three-hit” model that considers the individual’s genetic factors as a first “hit.” It has an immediate interaction with the early-life exposome (including persistent organic pollutants) that can be considered to be a second “hit.” Together, these first two “hits” produce a quiescent or latent phenotype, most probably encoded in the epigenome, which has become susceptible to a third environmental “hit” in later life. It is only after the third “hit” that the increased risk of disease symptoms is crystallised. However, if the individual is exposed to a different environment in later life, they would be expected to remain healthy. In this review, we examine the effect of exposure to persistent organic pollutants and particulate matters in early life and the relationship to subsequent neurodevelopmental and neurodegenerative disorders. The roles of those environmental factors which may affect epigenetic DNA methylation and therefore influence normal neurodevelopment are then evaluated.